Quality of Tectona grandis for sawn wood production - Albuês, T.A.S.; Pereira, B.L.C.; Carvalho, A.G.; Môra, R.; Oliveira, A.C. (Maderas. Ciencia y Tecnología, 2023)
Forestry companies have invested in genetic improvement to increase wood production in a shorter amount of time. Thus, studies are needed to compare the properties of clonal and seminal wood materials. The objective of this study was to analyze physical and mechanical properties of Tectona grandis from clonal (C1 and C2) and seminal (S) origin and evaluate the yield and quality of sawn wood subjected to outdoor and oven drying. Genetic material was collected from six, 15-year-old trees. Clone C2 presented the lowest amount of bark, and 51 % heartwood up to half the commercial height, while the heartwood of C1 and S went up to 25 % of the height. The three materials did not differ statistically for maximum angular deviation, pith eccentricity, basic density, Janka hardness, anisotropy, commercial income of sawn wood and the presence of knots. After the drying processes, the bowing and crooking indexes were less than 5 mm.m-1, however, the seminal material showed a higher cracking incidence after outdoor and oven drying. In conclusion, the wood properties of the three materials are similar. In addition, the oven drying process is recommended.